Pengungkapan Dan Pengukuran Aset Tetap Pada PT Kalla Electrycal System Makassar - Rukmana, Risa; Hasmi, Nurlaila (Universitas Patria Artha, 2020)
The purpose of this study was to determine the suitability of measurement and disclosure of fixed assets at PT Kalla Electrical System with measurement and disclosure of fixed assets according to PSAK No. 16 of 2017. The types of data used are qualitative data and quantitative data. The data sources used are primary and secondary data. Methods of data collection using interviews and observations related to research. The research was analyzed using comparative descriptive analysis method. The results of the study can be concluded and the measurement of fixed asset disclosure at PT Kalla Electrical System is not in accordance with the measurement and disclosure according to the Accounting Standard Statement (PSAK) No. 16 of 2017. This can be on the difference in measurement and disclosure of fixed assets regarding the termination and disposal of fixed assets at PT. Kalla Electrical System, there are still assets that have expired but are still used by the company in operational activities. Meanwhile, according to the Statement of Accounting Standards (PSAK) No. 16, fixed assets that have expired or have zero book value must be sold, destroyed, or granted so that the hypothesis is rejected.